2009
DOI: 10.1186/1472-6955-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Iranian nurses' constraint for research utilization

Abstract: Background: This paper identifies the views of Iranian clinical nurses regarding the utilization of nursing research in practice. There is a need to understand what restricts Iranian clinical nurses to use research findings. The aim of this study was to identify practicing nurses' view of aspects which they perceived constrain them from research utilization that summarizes and uses research findings to address a nursing practice problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
(66 reference statements)
2
23
0
Order By: Relevance
“…The professional development of nurses in this country has not progressed far and clinical nurses still imagine themselves as performers of doctors orders in addition to carrying out a few basic tasks. Such a view discourages the nurses from applying the extent of their knowledge and decision-making abilities directing them towards only obeying instructions (21) . In addition, most physicians in Iran are of the view that nurses are just following their commands and consequently are helpful, but are not seen as specialists in the delivery of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The professional development of nurses in this country has not progressed far and clinical nurses still imagine themselves as performers of doctors orders in addition to carrying out a few basic tasks. Such a view discourages the nurses from applying the extent of their knowledge and decision-making abilities directing them towards only obeying instructions (21) . In addition, most physicians in Iran are of the view that nurses are just following their commands and consequently are helpful, but are not seen as specialists in the delivery of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent research findings using the BARRIERS scale identified a few common perceived barriers, including inadequate time to read, interpret and implement new ideas of research findings [5,18]; knowledge deficits in accessing, understanding and evaluating research findings [8,15,26]; relevant research findings not being accessible in the workplace [6,18]; and lack of autonomy and authority to change practice [6,7]. Several aspects of nursing culture such as ritualistic care and lack of incentives to develop research-based practice have also been found to contribute to nurses’ perceived barriers to research utilization [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, much remains not to be understood about research utilization for improved nursing practice, especially in newly-industrialized, developing countries where nurses in the past have been little involved with research [7,8]. The factors facilitating and/or inhibiting research utilization in practice have not yet been identified in the health care system of mainland China, particularly in the discipline of nursing.…”
Section: Introductionmentioning
confidence: 99%
“…2004), relevant research findings being unavailable in the workplace (Funk et al. 1991a, 1995, Veeramah 1995, Retsas 2000) and lack of support from the institution and other practitioners, as well as lack of autonomy and authority to change practice (Veeramah 1995, Retsas 2000, Parahoo 2000, Sitzia 2001, Mehrad et al 2008, Salsali & Mehrdad 2009). Shortage of colleagues with the expertise to discuss research (Funk et al.…”
Section: Introductionmentioning
confidence: 99%
“…1991a, 1995, Kajermo et al. 1998, Salsali & Mehrdad 2009) and several aspects of nursing culture such as ritualistic care and no incentives to develop research‐based practice (Sitzia 2001) have also been found to contribute.…”
Section: Introductionmentioning
confidence: 99%